Digitalisasi Perbankan Syariah di Era VUCA - Kholifatul Husna Asri; Faridudin Malikur Rahmat (Neolectura, 2022)
The development of Islamic economics in society provides a central and influential role in the new economic order system with business models and innovations that are continuously updated by adjusting conditions without reducing the value of the Islamic economic system. This study aims to analyze the digitalization of Islamic banking in the VUCA era. The approach used is a qualitative approach. The results of this study are that the digitalization of Islamic banking must always harmonize with the development of increasingly developing technology and the presence of various kinds of application features that are offered to the public and are easy to use. In addition, digitalization in the VUCA era requires Islamic banks to innovate services in order to increase the effectiveness and efficiency of work processes and improve the quality of user or customer services. In an effort to achieve success in facing digitalization in the VUCA era, Islamic banks pay attention to several pillars, including 1) reducing costs in all operational activities offered, 2) implementing transparency and competitiveness in the face of business changes and 3) providing 24-hour customer service.